Sexualitet og imperialisme - Kledal, Anna Rebecca (Kvinder, Køn & Forskning, 1997)
The article deals with the construction of gender and sexuality in the colonial discourse. It is argued that sexuality is an important key to analysing relations between Europeans and non-Europeans, since sexuality was an area of institutionalization by the imperial administration. By deconstructing Western European imperialism, it is possible to identify many different, emerging discourses and the complex dependency between Western Europeans and non-Europeans.